Evaluation of Sinking-In and Cracking Behavior of Soda-Lime Glass under Varying Angle of Trigonal Pyramid Indenter - Yoshida, Satoshi; Wada, Ken; Fujimura, Takahiro; Yamada, Akihiro; Kato, Mitsuo; Matsuoka, Jun; Soga, Naohiro (Frontiers in Materials, 2016)
It is well known that glass undergoes elastic and inelastic deformation under a sharp diamond indenter. Although brittle or less brittle behavior of glass must be connected with such mechanical responses of glass under the indenter, there has been limited research on in situ deformation behavior of glass during the loading and unloading indentation cycle. This is because most indentation tests were conducted using a commercial hardness tester for which this information is not available. In this study, the in situ sinking-in region of glass during indentation test is determined using a custom-designed indentation microscope with trigonal pyramid indenters having different tip angles. It is found that both the shape of contact region and the amount of sinking-in are affected by indenter geometries and that the projected contact region of the glass sample under Berkovich indenter is not a regular triangle but a concave triangle with bowed-in edges. This is due to the larger amount of sinking-in under the face than under the ridge of indenter. It is also found that these deformation behaviors of glass are inseparably linked with contact damage or cracking in glass.